Meretas Jiwa Entrepreneur Muda Studi pada Salah Satu Desa Terbaik di Indonesia - Hanifah, Umi; Lestari, Retna Dewi; Nugroho, Novemy Triyandari; Wahyuningsih, Rita; Putri, Retno Karunia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Entrepreneur is a promising profession if it is occupied seriously for the future. On entrepreneur where they could get the opportunity to show their potential fully also could do a change and have freedom to reach the purpose they need without depending on others.Ngringo village as an economic point at Karanganyar regency which putting forward the entrepreneurship side. The independence power of community of Ngringo village has been tested independently by IPD (Development of Village Index) categorize as independent village. It is implied that the Ngringo villages community is much participated on independence as improving their economic. That statement is proved by Ngringo village which placed the 4th of 100 the best village in Indonesia released by village ministry, Development remote village, and transmigration on 2018.Entrepreneurial trend which carrying the economic creative in Ngringo village is developing nowadays, and more spreading by the social development that occurred. The actor of economic creative obviously that is the entrepreneur which actually a young age who trying a new one. The young people paradigm gives different color at Ngringo village. Therefore, the research is going to analyze the link between the spirit of young entrepreneur as an effort of economic creative improvement.This research is done at Ngringo village, Karanganyar regency. The data analyzing method which is used is qualitative method by phenomenology approach by collecting data technique, interview, observation and documentation.The output target is the released of national journal accreditation. The research is expected to be able to give additional insight for the reader and also as the reference of researches at University of Duta Bangsa Surakarta area at the future time.